A novel low-density thermal insulation gypsum reinforced with superplasticizers. (5th April 2021) - Cao, Wenxiang; Yi, Wei; Yin, Suhong; Peng, Jiahui; Li, Jing
Highlights: Both SNF and PC can improve the physical and mechanical properties of TIG. PC can significantly retard the hydration process of the fresh samples. PC improves the microstructure of TIG at a lower adsorption amount. TIG with low density, excellent workability and high strength was prepared. Abstract: A novel low-density thermal insulation gypsum (TIG) containing 40 wt% vitrified microsphere (VM), 0–0.5 wt% sulfonated naphthalene formaldehyde (SNF) and polycarboxylate (PC) superplasticizers was produced. The physical and mechanical properties, hydration process, microstructure, and adsorption behavior of TIG were investigated. The results showed that both PC and SNF significantly improved the workability and contributed to 96.8% and 87.1% increases in the compressive strength at the optimum dosages of 0.2 wt% and 0.5 wt%, respectively, which are determined by the maximum water reduction rate of 28%. By comparing with SNF, PC had a better retardation effect in hydration rate, a lower saturated adsorption amount and gave a more compact microstructure with a low porosity, thus leading to higher strength in the hardened TIG. A recommendation of 0.2 wt% PC was proposed.